Compressive Strength Studies on Recycled Binder Concrete - Nguyen, D. D.; Phan, V. T. (Engineering, Technology & Applied Science Research, 2021)
Recycled materials are gradually utilized in concrete. This paper examines the use of recycled binder in concrete. The compressive strength tests on concrete incorporating recycled binder instead of cement were carried out after 7, 14, and 28 days of curing. Cement was replaced by the recycled binder in ratios of 10%, 20%, and 30% by weight. The results show that the compressive strength of concrete is strongly affected by the percentage of the recycled binder. It has been found that the compressive strength decreases linearly with the increasing content of recycled binder. The recycled binder does not affect the strength development of concrete. In order to apply recycled waste to concrete as a binder, it is necessary to perform supplement research with appropriate additives to compensate for the loss of the compressive strength.